Atividade bloqueadora de anticorpos IgG específicos purificados de soros de pacientes atópicos a ácaros sobre a reatividade de IgE a Dermatophagoides pteronyssinus por ELISA inibição - Siman, Isabella Lima (2013)
One of the purposes of allergen-specific immunotherapy (SIT) is to modulate the humoral immune response against allergens with significant increases in allergen-specific IgG1 and IgG4 levels. These antibodies are associated with blocking activity by preventing IgE binding to allergen and leading to reduced inflammatory responses. This study aimed to investigate in vitro blocking activity of allergen-specific IgG antibodies on IgE reactivity to D. pteronyssinus (Dpt) in sera from atopic patients. Dpt-specific IgG antibodies were obtained from atopic sera and irrelevant IgG from non-atopic sera. IgG antibodies were purified by ammonium sulfate precipitation followed by Protein-G affinity chromatography and evaluated with regards to purity by SDS-PAGE and immunoreactivity by slot-blot and immunoblot assays. The blocking activity was evaluated by inhibition ELISA. The electrophoretical profile after salting-out precipitation showed an enrichment of high molecular weight proteins in the precipitated fraction and strongly stained bands in the ligand fraction after chromatography, compatible with molecular weight of human IgG. It was detected strong immunoreactivity to IgG, negligible to IgA, and no reactivity to IgE and IgM. Dpt-specific IgG fraction was capable to significantly reduce levels of IgE anti-Dpt, resulting in 35-51% inhibition of IgE reactivity to Dpt in atopic patient sera. Allergen-specific IgG antibodies purified using available and standardized methodology are able to inhibit IgE reactivity to Dpt allergen extract. In addition to the clinical symptoms improvement (subjective parameter), this approach reinforces that the intermittent measurement of serum allergen-specific IgG antibodies will be an important objective laboratorial parameter that will help specialists to follow their patients under SIT.